Community perspective analysis of Yogyakarta special region using K-means algorithm - Berlina, Laila Indah; Aesyi, Ulfi Saidata; Kharisma, Kharisma (Universitas Muhammadiyah Yogyakarta, 2024)
This study explores community perspectives on Yogyakarta, a culturally rich region in Indonesia known as